Penerapan Metode Design Thinking dalam Perancangan Website Kuis Online Menggunakan Figma di SMP Negeri 39 Semarang - Nathanael, Farrel; Razaq, Jeffri Alfa; Santoso, Dwi Budi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In early 2020 the world received a disaster where a new virus was discovered that could cause death if exposed to the virus. So that many activities are disrupted, one of which is teaching and learning. So that makes teaching and learning activities carried out online using a quiz website. The purpose of this research is to identify user needs in using an online quiz website. The Design Thinking method is a method for understanding users and defining problems and finding solutions to design. The result of the research that has been carried out is a quiz website design that can be used by teachers and students. The method used to test the results of the quiz website design is the System Usability Scale by giving questionnaires to teachers and students. From the results of the calculation of the questionnaire that has been distributed, it gets a value of 72, which means that the design results made are quite good.